2012
DOI: 10.1111/j.1549-8719.2012.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microcirculatory Responses of Insulin‐Resistant Rats are Preserved to Physiological and Pharmacological Stimuli

Abstract: Objective Previously we have shown that insulin resistance impairs the vascular reactivity of the major cerebral arteries of Zucker obese (ZO) rats prior to the occurrence of type-2 diabetes mellitus. However, the functional state of the microcirculation in the cerebral cortex is still being explored. Methods We tested the local cortical blood flow (CoBF) responses of 11–13 week-old ZO (n=31) and control Zucker lean (ZL, n=32) rats to several stimuli measured by laser Doppler flowmetry using a closed cranial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Our laboratory has shown that mitochondrial-dependent vasodilatory responses of major cerebral arteries are diminished in Zucker obese (ZO) rats (27,28). On the other hand, we have also shown that local cortical microcirculatory responses to pharmacological blood flow stimulators, such as bradykinin, N-methyl-Daspartate (NMDA), bicuculline, and physiologically induced hypercapnia, were not significantly altered in insulin-resistant ZO rats compared with phenotypically normal, Zucker lean (ZL) controls (24).…”
mentioning
confidence: 82%
“…Our laboratory has shown that mitochondrial-dependent vasodilatory responses of major cerebral arteries are diminished in Zucker obese (ZO) rats (27,28). On the other hand, we have also shown that local cortical microcirculatory responses to pharmacological blood flow stimulators, such as bradykinin, N-methyl-Daspartate (NMDA), bicuculline, and physiologically induced hypercapnia, were not significantly altered in insulin-resistant ZO rats compared with phenotypically normal, Zucker lean (ZL) controls (24).…”
mentioning
confidence: 82%
“…Another study using an ex vivo approach showed that MCA relaxation is also diminished in 17-week old obese male Zucker rats (201). However, cerebral microcirculatory responses were preserved as demonstrated by no changes in cortical blood flow in response to topical bradykinin application or carbon dioxide ventilation in 12-week old obese and lean animals suggesting that early preventive strategies can offer vasculoprotection for the microcirculation (127). Interestingly, two groups reported that impairment of endothelium-dependent relaxation occurred despite an increase in eNOS protein suggesting that enzyme activity was dysregulated in obese Zucker rats (223).…”
Section: Agonist-induced Cerebrovascular Reactivitymentioning
confidence: 99%
“…Assessing vascular control of blood flow can involve a variety of methods, such as the use of blood flow-pressure measurements (using thermodilution), 6 velocity measurements using Doppler 7 (assuming constant diameter), or the use of vascular flow probes. 8 Although these techniques certainly have advanced our understanding concerning the control of vascular resistance, they are indirect measurements and have potential inherent sources of error (eg, derived calculations).…”
Section: Assessing Vascular Control Of Blood Flowmentioning
confidence: 99%